How does neighborhood walkability affect obesity? The mediating role of commute mode - Yang, Wenyue; Zhen, Xinyu; Zhou, Suhong (Journal of Transport and Land Use, 2021)
The walkability of a neighborhood is closely related to residents’ travel behavior and daily life and, ultimately, their health and wellbeing. Although existing studies in this area have reached some enlightening conclusions, few of them have considered residents’ travel attitudes and preferences, or the mediating role of commute mode. Do travel attitudes and preferences matter in the relationship between neighborhood walkability and residents being obese? How does commute mode work as a mediator? To answer these questions, based on the 2019 travel survey data in Guangzhou, this paper uses the Multilevel Linear Model (MLM) to examine the association between neighborhood walkability and residents’ body mass index (BMI). Furthermore, the Mediation Model is used to identify the mediating role of commute mode in the relationship between walkability and BMI. The results show that (1) travel attitudes and preferences do affect the individual’s BMI through the mediator of commute mode. (2) After controlling the individual socio-demographics and travel attitudes and preferences, neighborhood walkability has a significant negative effect on BMI. Meanwhile, walkability has a significant positive effect on the use of non-private motorized commute modes. Non-private motorized commute modes have a significant negative effect on BMI. (3) The mediating effect of commute mode in the relationship of neighborhood walkability with the individual’s BMI is significant. The proportion of mediation is 32.90%. Insights into the relationship between neighborhood walkability, commute mode, and individual BMI highlight the importance of walkable neighborhoods that encourage people to use healthy commute modes.